(Pentamethylcyclopentadienyl)chloridoiridium(III) Complex Bearing Bidentate Ph2PCH2CH2SPh-κP,κS Ligand - Gerd Ludwig; Ivan Ranđelović; Dušan Dimić; Teodora Komazec; Danijela Maksimović-Ivanić; Sanja Mijatović; Tobias Rüffer; Goran N. Kaluđerović (Biomolecules, 2024)
The (pentamethylcyclopentadienyl)chloridoiridium(III) complex bearing a κP,κS-bonded Ph2PCH2CH2SPh ligand ([Ir(η5-C5Me5)Cl(Ph2P(CH2)2SPh-κP,κS)]PF6, (1)] was synthesized and characterized. Multinuclear (1H, 13C and 31P) NMR spectroscopy was employed for the determination of the structure. Moreover, SC-XRD confirmed the proposed structure belongs to the “piano stool” type. The Hirshfeld surface analysis outlined the most important intermolecular interactions in the structure. The crystallographic structure was optimized at the B3LYP-D3BJ/6-311++G(d,p)(H,C,P,S,Cl)/LanL2DZ(Ir) level of theory. The applicability of this level was verified through a comparison of experimental and theoretical bond lengths and angles, and 1H and 13C NMR chemical shifts. The Natural Bond Orbital theory was used to identify and quantify the intramolecular stabilization interactions, especially those between donor atoms and Ir(III) ions. Complex 1 was tested on antitumor activity against five human tumor cell lines: MCF-7 breast adenocarcinoma, SW480 colon adenocarcinoma, 518A2 melanoma, 8505C human thyroid carcinoma and A253 submandibular carcinoma. Complex 1 showed superior antitumor activity against cisplatin-resistant MCF-7, SW480 and 8505C cell lines. The mechanism of tumoricidal action on 8505C cells indicates the involvement of caspase-induced apoptosis, accompanied by a considerable reduction in ROS/RNS and proliferation potential of treated cells.